(untitled) (Philological Studies, 2019)
The classical study of Pygmalion effect was conducted in 1968 by Rosentahl and Jacobson on elementary school children. They find that teacher expectations can act as self-fulfilling prophecies because students’ achievements come to reflect the expectations. Pygmalion studies were also undertaken on nonschool organizations. In the work organizations it was found that people perform better when a leader has high expectations on them and shows confidence in them. Awareness and nonawarenes determinants of Pygmalion effect will be explained as well. Pygmalion Leadership Style and internal-external efficacy model will be presented. This model distinguishes between general and specific self-efficacy and between self-efficacy and collective efficacy. Beside Pygmalion effect the Galatea effect will also be presented, where self-produced expectations influence individuals whose own self-expectations have been raised. The negative impact of low teacher expectations on performance is colled Golem effect.